An alternative view of exchange market pressure episodes in emerging Europe: an analysis using Extreme Value Theory (EVT) - Frigyes Ferdinand Heinz; Desislava Rusinova (European Central Bank (ECB), 2015)
Using extreme value theory tools, we demonstrate that the distributions of the exchange market pressure (EMP) series for most of twelve emerging Europe countries have heavy tails, and disregarding their tail properties may lead to substantial underestimation of the probability of tail events. Using an extreme-value-based EMP crisis definition leads to a different set of crisis determinants compared to a definition based on standard errors. The probability of extreme EMP periods in our sample is affected by global risk aversion, regional contagion, the level of international reserves, foreign direct investment, history of past crises and accumulated domestic credit and real exchange rate related imbalances.
Keywords: C10; E44; F37; F32; G01; 330; Contagion; Currency crisis; Exchange market pressure; Extreme value theory; Macroeconomic imbalances